Echocardiographic Changes in Patients with End-Stage Renal Disease at Initiation of Dialysis (Journal of Renal and Hepatic Disorders, 2021)
Echocardiography is a simple and established method of evaluating cardiac functions, assessing left ventricle geometry, and systolic and diastolic functions. Patients with chronic kidney disease have a tremendous burden of cardiovascular disease (CVD), and patients with end-stage renal disease (ESRD) are at a greater risk of CVD and deaths. In this study, 245 incident dialysis patients were included, and none of the patient was on erythropoietin. All the patients were aged >18 years. Patients with ESRD, already on maintenance dialysis, were not included in this study. Patient’s data such as demographic details, comorbidities, laboratory values, echocardiographic changes, management, and outcome were recorded. Out of 245 patients, 165 (67.3%) were males and 80 (32.6%) females. The mean age of the patients was 49.7 years. Left ventricular hypertrophy (LVH) was observed in 188 (76.7%), mild left ventricular dysfunction (LVD) in 25.7%, moderate LVD in 23.67%, severe LVD in 8.5%, global hypokinesia in 33.8%, valvular heart disease in 26.5%, regional wall motion abnormality in 4.4%, and pericardial effusion in 1.6% patients. Echocardiographic changes, such as LVD, LVH, and global hypokinesia, were observed in greater number in hypertensive group com-pared to normotensive group (P < 0.05). On regression analysis adjusted for age and gender, we found that hypertension and anemia (
Keywords: echocardiography; hypertension; CKD